(untitled) (Research, Society and Development, 2022)
In 2015, the state of Pernambuco instituted the State Policy for the Comprehensive Health of Lesbians, Gays, Bisexuals, Transvestites and Transsexuals (PESILGBT) as a response to the health demands of these social groups. In this context, this article aims to evaluate the implementation of PESILGBT from its management instruments. A case study was carried out through documentary analysis and content analysis of the Management Instruments: State Health Plan; Annual Health Programs, and Annual Management Reports. Among the LGBT social groups, it was evidenced the greater insertion of health care actions directed at transvestites and transsexuals, demonstrating the increase in the visibility of these groups in the context of public health policies in Pernambuco. However, the perpetuation of the invisibility of lesbian and bisexual women in this same context was also observed. Regarding approaches in health education as strategies to change professional practice, the institutional commitment of the State Department of Health of Pernambuco was expressed with the elimination of prejudice and discrimination based on sexual orientation and gender identity in the state health network, this being one of the main obstacles to health care. It was concluded that in the current context of reemergence of neoliberal ideology, where there is no priority to equity policies, PESILGBT acts as an institutionalized instrument to strengthen the right to health of LGBT social groups.